The life of Robert Stephenson, F.R.S. etc. etc., late President of the Institution of Civil Engineers : with descriptive chapters on some of his most important professional works by William Pole, F.R.S., member of the Institution of Civil Engineers. Vol. I - Jeaffreson, John Cordy, 1831-1901 (Longman, Green, Longman, Roberts, & Green, 1864)
This first volume of biography covers: the Stephenson genealogy; Robert's childhood in Long Benton; his schooldays; his apprenticeship; his preparations for going to America and his time in South America; his return and settlement in Newcastle; his work on the construction of the London and Birmingham and the Newcastle and Darlington Railways, and on locomotive propulsion.